Produção do espaço, dinâmicas territoriais e vetores técnicos na zona costeira do estado do Pará: uma geografia da subsunção e das exterioridades: uma geografia das águas - SOARES, Daniel Araújo Sombra (Universidade Federal do Pará, 2023)
This Doctoral Thesis in Geography is a study case about the Brazilian State of Pará’s Coastal Zone as a spatial outline that synthesizes Amazonian particularities, and at the same time, clearly illustrates the constitutive and structuring Brazilian space formation elements. The investigation aims to understand the importance of land ownership (in a broad sense, involving water resources, in its multiple dimensions, thus being the property of land and water), for the reproduction of local elites as hegemonic agents, in the control of production of space, territorial ordering and in the regulation of forms and the value of labor. In the “compensatory activities”, we see a formal subsumption reproduction foundation that characterized the horizontal pact between local oligarchies that founded Brazilian space formation, which structures the Brazilian national state, after overcoming the particular spatial formations inherited from colonization. It defends the analysis of spatial structures, territorial dynamics and, particularly, the change in the development vectors of the State of Pará’s Coastal Zone as tools to understand the historical transition from formal to real subsumption in Brazilian space formation (which, in the Amazonian case, took place in the truculent form of the “Great Projects” imposition), with the production of counter spaces that materialize and spatialize the externalities of capital.